Atmospheric conditions conducive to marine fog over the northeast Pacific in winters of 1979–2019 - Li, Xinbei; Zhang, Suping; Koračin, Darko; Yi, Li; Zhang, Xin (Frontiers in Earth Science, 2022)
Observations show that the northeast Pacific (NEP) is a fog-prone area in winter compared with the northwest and central Pacific where fog rarely occurs in winter. By synthesizing observations and reanalysis results from 1979 to 2019, this study investigates the atmospheric circulation and marine atmospheric boundary layer structure associated with marine fog over the NEP in winter. Composite analysis shows that the eastern flank of the Aleutian low and the northwestern flank of the Pacific subtropical high jointly contribute to a northward air flow over the NEP. Under such conditions, warm and moist air flows through a cooler sea surface and facilitates the formation of advection-cooling fog. The air near the sea surface in foggy areas is cooled by the downward sensible heat flux. The smaller upward latent heat flux (∼10 W m−2) compared to the surrounding area (>60 W m−2) demonstrates that the moisture originates from the advection instead of local evaporation. The lower (at 925 to 875 hPa) and stronger (up to 0.08 K hPa−1) inversion layer, compared with cloudy cases and the turbulence in the lower atmosphere (below 975 hPa), also promotes fog formation and evolution. Approximately 68% of all fog cases (42242) show positive differences between surface air temperature (SAT) and sea surface temperature (SST), while 32% are negative, during southerly winds. Composite analysis of the latter shows lower specific humidity above the inversion bottom compared to the former. Dry air enhances longwave radiative cooling from the fog top, favoring cooling of the fog layer, gradually causing SAT to fall below SST.